Peer-to-peer transactive energy trading enabled decentralized energy management of a hybrid building cluster - Ying, Chenhao (Nanyang Technological University, 2024)
With a rising number of buildings being equipped with private distributed energy resources (DERs) such as rooftop PV panels and energy storage devices, an effective energy management method for a building cluster becomes increasingly imperative. This paper proposes a novel decentralized transactive energy management (TEM) method for a cluster of residential and commercial buildings, which enables peer-to-peer (P2P) energy trading among the DER owners and consumers, and addresses the operational challenge on the power network. Mathematically, the strategic interactions among the DER owners and consumers are captured by a multi-leader-multi-follower (MLMF) Stackelberg game and formulated as a bi-level model. The DER owners, the commercial and residential consumers are autonomous entities, optimizing their individual welfare functions and sharing necessary trading-related information, which are expressed as the upper-level leaders’ models and the lower-level followers’ models, respectively. To preserve the privacy and autonomy of each entity within the building cluster, a distributed algorithm incorporated with an efficient P2P pricing mechanism is designed for the formulated MLMF Stackelberg game problem. Simulation results demonstrate the effectiveness of the proposed method on reducing the reliance of the building cluster on the power grid, motivating the DERs to actively participate in P2P trading, and reducing the consumers’ costs on energy consumption.